PELAKSANAAN PEMBINAAN DI LEMBAGA PEMASYARAKATAN KELAS II B KOTA PAYAKUMBUH TERHADAP NARAPIDANA RESIDIVIS - Siti Azizah; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The development of convicts is an integral part of the law enforcement process, with the existence of a correctional system, it is hoped that Prison Inmates can become fully human regardless of the crimes they have committed, are aware of their mistakes, can improve themselves, and have no intention of repeating crimes again. However, the problem we are currently facing is that we still encounter or hear about perpetrators of crimes who are "relapsed" or are still committing crimes again, which are called recidivists. The purpose of this study is to analyze and describe the implementation of coaching in Correctional Institutions for recidivist convicts. The formulation of the problem in this study is how to implement coaching in correctional institutions for recidivist convicts. The method that researchers use in this study is a qualitative research method. The informants contained in this study were Correctional Officers in the coaching section and Correctional Assisted Residents. Data collection techniques used are in-depth interviews and observation. The analysis technique of this research uses Miles and Huberman to collect data, reduce data, and present data. The theory used to analyze the research findings is the structural functionalism theory from Talcott Parsons and the total institutional perspective according to Erving Goffman. Based on the results of the research, it was obtained: (1) The implementation of coaching in Class II B Correctional Institutions in Payakumbuh City for recidivist convicts has been running effectively and in accordance with correctional goals, (2) Obstacles faced during the implementation of coaching include internal factors from Prison Assisted Residents, and the excess residential capacity of Correctional Institutions. Keywords: Prisoner, Recidivist